Antibiotic Use in China’s Public Healthcare Institutions During the COVID-19 Pandemic: An Analysis of Nationwide Procurement Data, 2018–2020 - Yang, Ying; Geng, Xin; Liu, Xiaojun; Wen, Xiaotong; Wu, Ruonan; Cui, Dan; Mao, Zongfu (Frontiers in Pharmacology, 2022)
Background: The overuse of antibiotics is a serious public health problem and major challenge in China, and China lacks up-to-date evidence on the nationwide antibiotic use in different healthcare settings. The changes of China’s antibiotic use under the COVID-19 pandemic are still unknown. Objective: This study aimed to investigate the use of antibiotics in China’s public medical institutions based on a three-year nationwide surveillance, and to examine the impact of the COVID-19 pandemic on China’s antibiotic consumption. Methods: This study used nationwide drug procurement data from the China Drug Supply Information Platform (CDSIP). We retrospectively analyzed antibiotic procurement data of 9176 hospitals and 39,029 primary healthcare centers (PHCs) from 31 provinces in mainland China from January 2018 to December 2020. Antibiotic utilization was measured by defined daily doses (DDDs) and DDD per 1,000 inhabitants per day (DID). Generalized linear regression models were established to quantify the impact of COVID-19 pandemic on antibiotic use. Results: The total antibiotic consumption among all health care settings increased from 12.94 DID in 2018 to 14.45 DID in 2019, and then dropped to 10.51 DID in 2020. More than half of antibiotics were consumed in PHCs, especially in central regions (59%-68%). The use of Penicillins (J01C) and Cephalosporins (J01D) accounted for 32.02% and 28.86% of total antibiotic consumption in 2020. During 2018-2020, parenteral antibiotics accounted for 31%-36% of total antibiotic consumption, the proportion is more prominent in central and western regions and the setting of hospitals. Access category antibiotics comprised 40%-42% of the total utilization. Affected by COVID-19, the antibiotic consumption were significantly dropped both in hospitals (β= -0.11, p<0.001) and PHCs (β= -0.17, p<0.001), as well in total (β= -0.13, p<0.001). Significant increments were observed in the proportion of total antibiotics (β= 0.02, p=0.020) consumed in hospitals (against the consumption in all healthcare settings), as well as parenteral antibiotics (β= 1.76, p<0.001). Conclusion: The consistent preferred use of penicillin and cephalosporin, as well as injections, among China’s public healthcare institutions should draw concern. China’s antibiotic consumption significantly declined under COVID-19 pandemic, which brings opportunities for antibiotic use management in China.